An Israeli–Palestinian Hecuba: Hanoch Levin's Anti-Tragedy. (30th August 2021) - Akavia, Abigail
Abstract: The Lost Women of Troy by Hanoch Levin, Israel's foremost playwright of the twentieth century, is an adaptation of Euripides' Trojan Women and Hecuba . Staged in Tel Aviv in 1984 during the First Lebanon War, Lost Women focuses on the bereavement and humiliation of Hecuba. Levin reconfigures this character to reflect mothers on both sides of the Israeli–Palestinian conflict. Through a subversion of the aesthetics of tragedy, Levin's play is an indictment of the notion of heroism prevalent in Israeli society. It presents a bitter criticism of his public's acceptance of the ideology of war and their participation in a narrative that glorifies those who die in combat as heroes. Levin's critique, I argue, is formulated as a textual sparagmos, a violent tearing apart of Euripides' tragedies and the conventions in which they operate. Levin's metatheatrical violence against the tragic genre parallels the inherent violence of the discourse of heroism which his adaptation seeks to expose and denounce.